A Guide to Developing Safety Protocols for International Craniofacial Outreach Programs During the COVID-19 Era. Issue 1 (January 2021) - Salehi, Parsa P.; Johnson, Adam B.; Rubinstein, Brian; Pahlavan, Nima; Azizzadeh, Babak; Hamdan, Usama S.
Abstract : Abstract: The ongoing COVID-19 outbreak has created obstacles to health care delivery on a global scale. Low- and middle-income countries (LMICs), many of which already suffered from unmet surgical and medical needs, are at great risk of suffering poor health outcomes due to health care access troubles brought on by the pandemic. Craniofacial outreach programs (CFOP)—a staple for craniofacial surgeons—have historically provided essential care to LMICs. To date, there has not been literature discussing the process of resuming CFOP mission trips. Herein, we propose a roadmap to help guide future journeys, as well as summarize practical considerations.